The Role of Maladaptive Schemas in Pain Perception and Pain Acceptance in Patients with End‑Stage Cancer - Cheraghi, Monir; Khalatbari , Javad; Ahadi, Hasan (Mental Health and Lifestyle Journal, 2026)
The present study aimed to examine pain perception and pain acceptance in patients with end‑stage cancer based on maladaptive schemas. In terms of purpose, the study was applied research, and in terms of methodology it employed a correlational design. The statistical population of the present study consisted of all patients with end‑stage cancer at Imam Khomeini Hospital in Tehran, totaling 300 individuals. Using a random sampling method, 150 patients were selected as the study sample, and the questionnaires were distributed among them. The instruments used included the Young Schema Questionnaire (YSQ‑SF; Young, 1988) and the McGill Pain Questionnaire (MPQ; Melzack, 1975). The data were analyzed in two sections—descriptive and inferential—using SPSS version 23. The results of the statistical analyses indicated that there was a significant relationship between all maladaptive schema variables and pain perception and acceptance. The correlation coefficient between rejection and pain perception and acceptance was 0.674, which was statistically significant (p < .05). Furthermore, a significant relationship was found between other components and pain perception and acceptance. The raw and standardized coefficients in the regression analysis indicated that the standardized coefficient was 0.727 and the unstandardized coefficient was 0.17.